DOI Analisis Spasial Perubahan Tutupan Vegetasi dan Suhu Permukaan di Kota Cirebon Menggunakan Data Penginderaan Jauh - Yaasin, Muhammad Hikmal; Devrian, Muhammad Rafi; Muttaqin, Rizkia Ananda (Jurnal Sains Geografi, 2025)
Changes in vegetation cover due to urbanization in Cirebon City have a significant impact on land surface temperature and the Urban Heat Island (UHI) phenomenon. This study analyzes vegetation distribution and surface temperature changes from 2018 to 2025 using Landsat 8 imagery with NDVI, LST mapping, and change detection methods. The results indicate that vegetation loss is associated with rising temperatures and the intensification of UHI, while areas with preserved vegetation exhibit lower temperatures. These findings highlight the importance of preserving and expanding green open spaces as a mitigation strategy against land use change impacts and rising urban temperatures.